Jurnalisme Investigasi dalam Novel Kincir Waktu Karya Akmal Nasery Basral - Lina Sari; Ahmad Harun Yahya; Jufrizal Jufrizal (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The press plays an important role in disseminating information and carrying out its social control function. One form of journalism is investigative journalism, which involves searching, collecting, verifying, and thoroughly examining information to uncover facts that are not yet known to the public. This process is represented in the novel Kincir Waktu by Akmal Nasery Basral, which portrays journalists’ efforts to uncover facts related to the May 1998 Riots. This study aims to analyze the process of investigative journalism represented in Kincir Waktu. The study employs a descriptive qualitative approach using the Miles and Huberman interactive data analysis model. The analysis is based on Dandhy Dwi Laksono’s concept of investigative journalism. The findings show several stages, including team formation, initial research and observation, determining the angle and hypothesis, strategic planning, evidence gathering through material trails, people trails, and money trails, as well as collecting testimonies. Thus, the novel represents investigative journalism as a systematic process of uncovering facts for the public.